Membros: v. 16, n. 2 (2018) - ., . (RENOTE, 2018)
Aliane Krassmann - PGIE/UFRGS Ana Carolina B de Marchi - UPF Ana Marli Bulegon - UNIFRA Andreia Rosangela Kessler Muhlbeier - PPGI/UFSM Cícero Costa Quarto - Universidade Estadual do Maranhão (UEMA) Christian Brackmann - Instituto Federal Farroupilha Elisa Boff - UCS Eliseo Reategui - FACED/PGIE - UFRGS Erico Amaral - UNIPAMPA Fabiana Sgobbi - UFRGS Fabrício Herpich - PGIE/UFRGS Felipe Becker Nunes - PGIE/UFRGS Giliane Bernardi - UFSM Gilse Antoninha Morgental Falkembach - UFSM/CINTED Gleizer Voss - Instituto Federal Farroupilha Heli Meurer - UNIRITTER Janete Sander Costa - ULBRA Ketia Kellen da Silva - UFRGS Leandro R Tibola - URI Liane Margarida Rockenbach Tarouco - CINTED/FACED/PGIE - UFRGS Marcelo Augusto Rauh Schmitt - Instituto Federal do Rio Grande do Sul Marcelo Foohs - FACED /UFRGS Marcia Notare - Instituto de Matemática/UFRGS Marcus Vinícius de Azevedo Basso - Instituto de Matemática/UFRGS Marlise Geller - ULBRA Marta Bez - FEEVALE Otavio Costa - UFRGS Patrícia Campelo Costa Barcellos - UFRGS Querte Mehlecke - FACCAT/RS Ramon Rosa Maia Vieira Junior - PPGIE/UFRGS Renato Dutra - Universidade Anhembi Morumbi Ricardo Azambuja Silveira - INF/UFSC Roberto dos Santos Rabello – UPF Rodrigo Silva - UFRGS Rodrigo Machado - UFRGS Rodrigo de Oliveira Soares - UFRGS Roseclea Medina - UFSM Valéria Machado da Costa – Fiocruz Valter Ferreira - UFRGS Vinicius Hartmann Ferreira - UFRGS Coordenação : Liane Margarida Rockenbach Tarouco - CINTED/UFRGS Eliseo Reategui - PGIE/UFRGS